Bapak Rumah Tangga: Sebuah Alternatif Profesi? - Suharmanto, Toto; Muhaimin, Muhaimin; Santoso, Ignatius Hari (JURNAL BISNIS STRATEGI, 2020)
The development of economy in the world makes females have a large opportunity to pursue their career and become the breadwinner. In the other side, so many male that willing to resign from the job and become househusband. This research aims to test the difference of male and female attitude regarding the househusband as profession in our society. The samples used in this research is 200 respondent, consist of 108 male respondents, and 92 female respondents. Using the technique of Mann Whitney statistical test, this research provide the result that there is no difference attitude of male and female toward househusband as profession in our society. Even male and female, as together do not accept this new profession, both are agree that married man should take active role to manage domestic issue in the house, including child caretaking.Â Key Words : househusband, role reversal, attitude difference